Karakterisitik Bakso Ikan Patin (Pangasius pangasius) dengan Penambahan Karagenan, Isolat Protein Kedelai, dan Sodium Tripolyphospat - Dina Defyanti Sinaga; Herpandi Herpandi; Rodiana Nopianti (Universitas Sriwijaya, 2017)
The purpose of this research was to investigate the characteristics of catfish meatball with addition of isolate soy protein, carrageenan and STPP. The Research used a Randomized Block Design (RDB) with five addition of food additives (carrageenan 2%, STPP 0.3% and isolate soy protein 7%). Each treatment was replicated two times. The attributes observed were physical analysis (expressible moisture content, gel strength and folding test), chemical analysis (moisture content, protein content and fat content) and sensory analysis (aroma, taste and colour). The result showed the average value of expressible moisture content was ranged from 0.52%-1.72%, gel strength was 79-172 gf, folding test was 2-4, moisture content was 70.14%-75.41%, protein content was 3.98%-7.13% and fat content was 1.4%-2.16%. Sensory analysis for colour of meat ball was ranged from 3.88-4.56, taste 3.8 - 4.56 and aroma 3.88-4.44. Addition of food additives into catfish meatballs significantly affect (p<0.05) to expressible moisture content, gel strength, protein content, aroma, taste and folding test. But did not significant affect about moisture content, fat content and colours. The chemical analysis showed kind of food additive that can replace the STPP is isolate soy protein. And according to physical analysis the food additive than can repace STPP is combination isolate soy protein and carrageenan as well on the analysis of sensory analysis.